Aquatic invasion patterns across the North Atlantic. (11th December 2021) - Cuthbert, Ross N.; Kotronaki, Syrmalenia G.; Carlton, James T.; Ruiz, Gregory M.; Fofonoff, Paul; Briski, Elizabeta
Abstract: Biological invasions are a major driver of biodiversity loss and socioeconomic burden globally. As invasion rates accelerate worldwide, understanding past invasion dynamics is essential to inform predictions of future invaders and impacts. Owing to a high diversity of pathways and current biosecurity gaps, aquatic systems near urban centres are especially susceptible to alien species establishments. Here, we compiled and compared alien species lists for three different aquatic recipient regions spanning the North Atlantic: Chesapeake Bay, Great Lakes‐St. Lawrence River and North and Baltic Seas. Each system is a major trade centre, with a history of invasions, and characterized by a strong natural salinity gradient. Our goal was to compare the alien species across systems, to test for similarities in the taxonomic composition and geographic origin as well as species overlap among the three regions. We selected specific macroinvertebrate, algal and fish taxa for analysis, to control for uneven taxonomic and biogeographic resolution across regions. Cumulatively, we identified 326 individual alien species established in these aquatic systems, with the North and Baltic Seas most invaded overall (163), followed by Great Lakes‐St. Lawrence River (84) and Chesapeake Bay (79). Most invasions were from Ponto‐Caspian, Eurasian, Northwest Pacific, Northwest Atlantic and North American origins, and mostly comprised Arthropoda, Chordata, Mollusca and Annelida. However, origins and taxonomies differed significantly among destinations, with Ponto‐Caspian species particularly successful invaders to the North and Baltic Seas then Great Lakes‐St. Lawrence River, but less so to Chesapeake Bay. Nevertheless, approximately eight‐tenths of invaders established in only one region, indicating disparate invasion patterns and a high potential for future aliens to accrue from increasingly diverse source pools and pathways. These results support biosecurity strategies that consider a broad range of geographic origins and taxonomic groups to limit the translocation, arrival and spread of alien species worldwide. Abstract : We compiled and compared alien species lists for three different aquatic recipient regions spanning the North Atlantic: Chesapeake Bay, Great Lakes‐St. Lawrence River and North and Baltic Seas. In total, we identified 326 alien species established in these aquatic systems, with most invasions from Ponto‐Caspian, Eurasian, Northwest Pacific, Northwest Atlantic and North American origins, and mostly comprising Arthropoda, Chordata, Mollusca and Annelida overall. However, origins and taxonomic compositions of alien species differed significantly among the recipient regions, with the vast majority of species invading only one region, suggesting disparate patterns and high potential for future invasions.